علاقة الضغوط النفسية بالتحصيل الدراسي لدى المعاقين بصريا - بوضبية، إيمان (جامعة الوادي university of eloued, 2018)
"ملخص الدراسة: هدفت الدراسة الى الكشف عن الضغوط النفسية لدى المعاقين بصريا وعلاقتها بالتحصيل الدراسي وذلك من خلال طرح التساؤلات التالية: هل هناك علاقة بين الضغوط النفسية والتحصيل الدراسي لدى المعاقين بصريا وفق متغير الجنس(ذكر، انثى)؟ هل هناك علاقة بين الضغوط النفسية والتحصيل الدراسي لدى المعاقين بصريا وفق متغير المستوى الدراسي (ابتدائي، متوسط، ثانوي، جامعي)؟ ولقد اعتمدت الدراسة على المنهج الوصفي الارتباطي، وتم استخدام الأداة لجمع البيانات المتمثلة في استبيان الضغوط النفسية، والذي وزع على عينة استطلاعية مكونة من (30) فردا والدراسة الاساسية مكونة من (33) فردا من تلاميذ وطلاب من مستوى ابتدائي ومتوسط وثانوي وجامعي بولاية الوادى، وقد تم استخدام الاساليب الاحصائية في حساب النتائج هو معامل الارتباط بيرسون واختبار Ttest واختبار انوفا وبعد تطبيق المقياس تم التوصل الى النتائج التالية: - لا توجد علاقة بين الضغوط النفسية لدى المعاقين بصريا والتحصيل الدراسي - لا توجد فروق ذات دلالة احصائية في الضغوط النفسية لدى المعاقين بصريا تعزى لمتغير الجنس - لا توجد فروق ذات دلالة احصائية في الضغوط النفسية لدى المعاقين بصريا تعزى لمتغير المستوى الدراسي. "Summary: The aim of the study was to uncover the psychological pressures of the visually impaired and their relation to the educational achievement by asking the following questions: Is there a relationship between the psychological pressure and educational achievement of the visually impaired according to the variable sex (male, female)? Is there a relationship between the psychological pressure and the academic achievement of the visually impaired according to the variable level of study (primary, intermediate, secondary, university)? The study was based on a descriptive descriptive approach. The tool was used to collect data from the psychological stress questionnaire, which was distributed to a sample of 30 individuals and the basic study consisting of 33 students from elementary, intermediate, secondary and university level in the wadi state, The statistical methods used in the calculation of the results were Pearson correlation coefficient, Ttest test and ANOVA test and after applying the scale the following results were obtained: - There is no relationship between the psychological pressure of the visually impaired and academic achievement - There are no statistically significant differences in the psychological pressures of the visually impaired due to the gender variable - There are no statistically significant differences in the psychological pressures of the visually impaired due to the variable of the academic level.
دراسة ميدانية بولاية الوادي
مذكرة ماستر في علوم التربية تخصص تربية خاصة
Keywords: الضغوط النفسية، التحصيل الدراسي، الإعاقة البصرية; Stress psychologique, réussite scolaire, déficience visuelle; Psychological stress, academic achievement, visual impairment